Changes in abortion access after implementation of Medicaid coverage in Illinois: a retrospective analysis - Terri-Ann Thompson; Carmela Zuniga; Danielle Young; Valeria Hernandez; Debra Stulberg; Lee Hasselbacher; Ashley McHugh; Hanz Dismer (BMJ Public Health)
Introduction In 2018, Illinois implemented House Bill 40 (HB-40), allowing state funds to provide Medicaid coverage for abortion. This study aimed to quantitatively measure changes in access among Illinois residents after the law’s implementation, with a focus on changes experienced by Medicaid versus non-Medicaid patients.Methods We conducted a retrospective analysis using 67 462 abortion visits across 18 health centres comparing service delivery patterns 1 year before and 3 years after HB-40 implementation. We used a t-test and difference-in-differences regression to assess the policy’s effect on mean gestational age at the time of abortion among Medicaid patients and non-Medicaid patients. We used χ2 tests to capture differences in insurance type used for payment, as well as differences between Medicaid and non-Medicaid patients in presenting at ≤11 weeks gestation, abortion method provided and time between scheduling and getting an abortion.Results From 2017 to 2020, the overall volume of abortions increased by 27% and the share of abortions paid for with Medicaid increased from 15% to 49%. Compared with non-Medicaid patients, Medicaid patients experienced a significant decrease in average gestational age at the time of abortion post-HB-40 (incidence rate ratio (IRR)=0.93, 95% CI 0.91 to 0.95, p<0.001). The proportion of Medicaid patients ≤11 weeks gestation increased post-HB-40 (76% to 83%; p<0.001) but did not change among non-Medicaid patients (89% to 90%; p=0.62). By 2020, the 13%-point gap that existed between the two groups in 2017 (76% and 89%) was reduced to 4 (86% and 90%). The proportion of medication abortions increased substantially for Medicaid patients post-HB-40 (27% to 46%; p<0.001) and increased slightly for non-Medicaid patients (51% to 53%; p=0.001), resulting in decreased gaps in medication abortions received between the two groups.Conclusion Medicaid coverage of abortion reduced insurance-related disparities for Medicaid patients, as shown by decreased gaps in average gestational age among Medicaid and non-Medicaid patients. It was also associated with increased medication abortions among Medicaid patients.